EVALUASI HASIL PEMERIKSAAN KESEHATAN BERKALA TERHADAP KESEHATAN PEKERJA PENYEMPROT PESTISIDA DI PT. LANGKAT NUSANTARA KEPONG DESA BUKIT LAWANG - wini anggraini; halinda sari lubis; kalsum * (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT The research was conducted on pesticide spraying workers at PT.LNK Kebun Bukit Lawang, Bahorok Subdistrict, in 2014, in order to evaluate their working condition. The researh was descriptive with cross sectional design. The population was 16 workers, and all of them were used as the samples, using total sampling technique. The data were gathered by using data obtained from the company such as the number of workers and the history of the company. Clinical data of the company were viewed from assessment form in the company clinic, based on the history of the previous illness and smoking. When the workers were intoxicated seriously, they had to be checked in the laboratory for examining the cholinesterase enzyme. Based on the distribution frequency, it was found that 12 respondents (75%) were women, 9 respondents (56,3%) were >50 years old with (62,5%) of them had length of service of less than 30 years, 12 respondents (75%) did not smoke, and 16 respondents (100%) had abnormal cholinesterase enzyme with 12 of them (75%) suffered from seriously acute intoxication, two of them (12,5%) suffered from mild intoxication, two of them (12,5%) suffered from chronic intoxication, and 10 respondents (62,5%) had the most history of illness. It is recommended that the workers in the pesticide spraying avoid contact with pesticides or move to non-chemical department temporarily until they are free from cholinesterase enzyme and return to normal